A morphometric evaluation of nasal septum in rhinosinusitis patients and association with its severity - Abdullah, Abdul Mokhti (2016)
INTRODUCTION The role of nasal septum in rhinosinusitis patient still remain unclear. Given the high incidence of deviated nasal septum in the population, the study about their association with rhinosinusitis is interesting. There are conflicting data in literatures regarding the role of DNS in rhinosinusitis, it is worth in studying this subject to give some input in this field of knowledge. By knowing the association between the DNS and rhinosinusitis one step ahead can be advocated in the management of rhinosinusitis. OBJECTIVES The aim of the study was to evaluate the morphometry of nasal septum in rhinosinusitis patient and to associated with its severity. To look for association between angulation and type of DNS based on Mladina classification with severity of rhinosinusitis based on symptom score, visual analogue scale ( VAS ) and CT scan score. METHODOLOGY A cross sectional study was done in which we evaluated 98 rhinosinusitis patients for symptoms severity and reviewed their CT scan of paranasal sinus . Their CT scan paranasal sinus obtained was 3.0 mm thicknesses in axial and coronal planes with high resolution technique. Symptoms severity was assessed via symptoms score and visual analogue scale (VAS). Whereas type of DNS according to Mladina classification, degree of septal angle deviation and CT scan score were obtained by reviewed the CT scan. The data were analysed using One Way ANOVA test. RESULT The prevalence of angulation and type of DNS were recorded: normal (angulation < 5o ) in 7 cases (7.1%) , mild (angulation 5o – 10o ) in 54 cases (55.1%), moderate (angulation 10.1o – 20o ) in 37 cases (37.8%) and no subject in severe ( > 20o) category. In term of Mladina type, majority are type 1 in 33 cases (32.6%) followed by type 3 in 27 cases (26.5%), type 4 in 14 cases (15.3%), type 2 in 12 cases (12.2%), type 6 in 8 case (8.2%), type 5 in 4 cases (5.1%) and type 7 are nil. Majority of the patient (62.0%) had a moderate symptom score, visual analogue scale and ct scan score. There was an association between angulation of DNS with severity of rhinosinusitis based on symptom score, visual analogue scale (p<0.05). There were no association between CT scan score and Mladina type of DNS with severity of rhinosinusitis (p>0.05). CONCLUSION Septal deviation angle of DNS play a role in rhinosinusitis as there was an association between severity of septal deviation angle with severity of rhinosinusitis. The more severe the septal angle deviation the more likelihood the severity of rhinosinusitis. However there were no association between type of DNS based on Mladina classification with severity of rhinosinusitis.